La proposta per la riforma del Regolamento «Bruxelles I» e i provvedimenti provvisori - Seatzu, Francesco (CUADERNOS DE DERECHO TRANSNACIONAL, 2011)
The proposed regulation aimed at amending (EC) regulation no. 44/2001 (hereinafter the “Brussels I regulation”), presented by the Commission on 14th of December 2010, seeks to modify, inter alia, the rules governing the allocation of jurisdiction for provisional and protective measures ordered by a court which does not have jurisdiction on the substance of the matter. According to the proposal, the court where proceedings on the substance are pending and the court that is addressed in relation to provisional measures, should cooperate in order to ensure that all circumstances of the case are taken into account when a provisional measure is granted. The Commission’s proposal further provides for the free circulation of those measures that have been granted by a court having jurisdiction on the substance of the case, including – subject to certain conditions – of measures which have been granted ex parte. On the background of these revisions lies a decision adopted by the drafters of the proposal: the choice of making provisional measures ordered by a court other than the one having jurisdiction on the substance unenforceable in another Member State, in view of the large divergence of national law on this issue and to avoid the risk of abusive forum-shopping. The article supplies a critical evaluation of the suggested amendments. It also deals with an issue, strictly related to the foregoing: that is the definition and meaning of “provisional and protective measures” under the new Brussels I regulation.